Influence of women in Dutch finance 1898-1940 - Joke Mooij (IBF - Institut für Bank- und Finanzgeschichte e.V., 2025)
– This paper focuses on the economic and societal impact of women in the Dutch financial sector during the period 1898-1940 by examining a dozen organisations in banking, insurance as well as brokerage, and by examining a dozen pioneering women with senior positions in finance. During this period, a growing number of well- educated women gained access to a broader range of economic activities and jobs. The organisations and the pioneering women contributed to a public recognition of women as finance professionals and as autonomous clients. Having more women in finance also enabled other women to better manage their finances, meet their credit demand, and insure against occasional loss of income. These developments contributed to female participation and economic growth.
Keywords: G21; G22; G24; J16; L26; N23; N24; 330; Financial Sector; Gender; Entrepreneurship; Europe